Poverty Reduction Strategies in Canada: A new way to tackle an old problem? - Notten, Geranda; Laforest, Rachel (Université d'Ottawa | University of Ottawa, 2016)
Since the end 1990s, jurisdictions across the world have adopted an innovative governance process called a Poverty Reduction Strategy (PRS). PRS processes are a perfect example of a new governance dynamics in which collaboration between the public sector and the community sector is leveraged to develop policy solutions to complex problems such as poverty. Jurisdictions argue that this new process helps ensure continued prioritization, improved information for decision making, and improved coordination between different units of government and other partners. In Canada nearly all provinces and territories now engage in a PRS process. This paper asks whether the PRS processes, as implemented by four Canadian provinces (Manitoba, Newfoundland and Labrador, Ontario and Quebec), have the potential to deliver on the expected governance benefits. This research is the first to connect theory to a widespread yet under-researched practice in government. We review the collaborative governance and performance management literatures for theories and empirical evidence on the costs and benefits of similar practices. We use official documents to identify a theory of change which explains how PRS processes could result in more poverty reduction. We use public information to describe and compare PRS processes in the four provinces. Our research shows that each province makes quite different choices in implementing its process and that such differences likely influence the degree to which aspired governance benefits are realized. When legislation supports the PRS process, provinces have more continuous activities and, where legislation details the role of non-government stakeholders, stakeholder involvement is more substantive and visible. There is now more public information on government’s actions but also still much scope for improvement, especially in linking fiscal expenses, effects of policy actions, and wellbeing outcomes. Whether new coordination mechanisms have been sufficient to yield substantive benefits in coordination is unclear.
Keywords: Poverty reduction strategy (PRS); Poverty reduction; Collaborative governance; Performance management; Social policy